2020
DOI: 10.21673/anadoluklin.720116
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell stabilizers as a supportive therapy can contribute to alleviate fatal inflammatory responses and severity of pulmonary complications in COVID-19 infection

Abstract: SARS-CoV-2(COVID-19) leads to severe acute respiratory syndrome by settling the pulmonary system. Mast cells (MCs) are multifunctional immune cells that are extensively distributed throughout the body and mostly present in pulmonary system. MCs play a vital role in acquired and innate immunity, and to maintain immune homeostasis of the body through a wide range of mediators in their cytoplasmic granules. Severe acute respiratory syndrome with proinflammatory cytokine release and pneumonia during COVID-19 infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…These studies thus suggest that targeting the PGD 2 – DP1 receptor pathway may be helpful to control SARS‐CoV infection in older humans. Furthermore, SARS‐CoV‐2 may cause mast cell activation via the toll‐like receptors (TLRs) or inducing crosslink of IgE–FcεRI and subsequent production of PGD 2 , where use of mast cell stabilisers, including β‐adrenoceptor agonists, is highlighted as potential therapeutic targets during SARS‐CoV‐2 infection due to their efficient inhibition of PGD 2 release (Kilinç & Kilinç, 2020). Infection with respiratory syncytial virus (RSV) up‐regulates HPGDS expression and increases PGD 2 secretion by cultured human primary airway epithelial cells (Werder et al, 2018).…”
Section: Pgs In Covid‐19: Possible Immunopathological Mechanismsmentioning
confidence: 99%
“…These studies thus suggest that targeting the PGD 2 – DP1 receptor pathway may be helpful to control SARS‐CoV infection in older humans. Furthermore, SARS‐CoV‐2 may cause mast cell activation via the toll‐like receptors (TLRs) or inducing crosslink of IgE–FcεRI and subsequent production of PGD 2 , where use of mast cell stabilisers, including β‐adrenoceptor agonists, is highlighted as potential therapeutic targets during SARS‐CoV‐2 infection due to their efficient inhibition of PGD 2 release (Kilinç & Kilinç, 2020). Infection with respiratory syncytial virus (RSV) up‐regulates HPGDS expression and increases PGD 2 secretion by cultured human primary airway epithelial cells (Werder et al, 2018).…”
Section: Pgs In Covid‐19: Possible Immunopathological Mechanismsmentioning
confidence: 99%
“…Histamine involvement in COVID-19 progression has been suggested and/or described in several reports (P. J. Barnes, 1991;Hill, 1992;Kilinc et al, 2020;Kritas et al, 2020). The anti-histaminic potential of HFE, again demonstrated in this study by HFE inhibition of both acute and chronic oedema due to CFA, could play a role in modulating the dysregulated immune response in COVID-19.…”
Section: Discussionmentioning
confidence: 90%
“…Histamine plays a central role in acute in ammation and anaphylaxis (Branco et al, 2018) ( Winbery & Lieberman, 2002). Relevant to COVID-19, histamine release from mast cells is known to mediate bronchoconstriction (Barnes, 1991;Hill, 1992;Kilinc et al, 2020;Kritas et al, 2020), and has been implicated in the progression of oedema observed in COVID-19 pulmonary disease (Malone et al, 2020).…”
Section: Discussionmentioning
confidence: 99%